A highly nitrogen-doped porous graphene – an anode material for lithium ion batteries. Issue 35 (12th August 2015) - Sui, Zhu-Yin; Wang, Caiyun; Yang, Quan-Sheng; Shu, Kewei; Liu, Yu-Wen; Han, Bao-Hang; Wallace, Gordon G.
Abstract : Highly porous nitrogen-doped graphene material obtained via melamine–formaldehyde resin as a cross-linker demonstrates excellent electrochemical properties in Li-ion batteries. Abstract : A novel nitrogen-doped porous graphene material (NPGM) was prepared by freeze-drying a graphene/melamine–formaldehyde hydrogel and subsequent thermal treatment. The use of melamine–formaldehyde resin as a cross-linking agent and nitrogen source enhances the nitrogen content. NPGM possesses a hierarchical porous structure, a large Brunauer–Emmett–Teller surface area (up to 1170 m 2 g −1 ), and a considerable nitrogen content (5.8 at%). NPGM displays a discharge capacity of 672 mA h g −1 at a current density of 100 mA g −1 when used as an anode material for lithium ion batteries, much higher than that observed for a nitrogen-free graphene porous material (450 mA h g −1 ). The NPGM electrode also possesses superior cycle stability. No capacity loss was observed even after 200 charge/discharge cycles at a current density of 400 mA g −1 . The enhanced electrochemical performance is attributed to nitrogen doping, high specific surface area, and the three-dimensional porous network structure.